Prestasi Akademik Mahasiswa Program Studi Kesehatan Masyarakat Dilihat Dari Kecerdasan Emosional Dan Efikasi Diri - Evi Ni'matuzzakiyah (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2020)
Background of Study : the progress of modern society can be achieved by the presence of educational institutions as an effort to educate the nation's life. The ongoing education process has a standardization of values achieved by students through the teaching and learning process. The quality of students can be seen from the academic achievements they have achieved. The flow of globalization with various challenges, the ability to control one's own emotions is a very important to be yourself, in addition to the role of self-efficacy, in the end with high emotional intelligence and self-efficacy will contribute to the learning process of students and improve their academic achievement . Methods : the study design was quantitative with a population of all students of Surya Global Health Science College of Public Health, a sample of 133 students Data from three scales; Emotional Intelligence, Self-Efficacy, and Academic Achievement will be analyzed using statistical techniques, namely simple regression analysis and multiple regression. Results : There was a significant influence between emotional intelligence and self-efficacy on the academic achievement of students of Surya Global Health Science College of Public Health, which Freg = 3,922 and p = 0,022 (p 0,05). Conclusion : Emotional intelligence and self-efficacy have a positive effect on academic achievement. Keywords : emotional intelligence, self-efficacy, academic achievement. Korespondensi : Evi NI’matuzzakiyah, STIKES Surya Global Yogyakarta Blado Potorono Banguntapan, Bantul, DIY, Indonesia, 081568417511, evizakiyahnazhif@gmail.com